Separating parental and treatment contributions to perinatal health after fresh and frozen embryo transfer in assisted reproduction: A cohort study with within-sibship analysis. - Kjersti Westvik-Johari; Liv Bente Romundstad; Deborah A Lawlor; Christina Bergh; Mika Gissler; Anna-Karina A Henningsen; Siri E Håberg; Ulla-Britt Wennerholm; Aila Tiitinen; Anja Pinborg; Signe Opdahl (PLoS Medicine)
Background Compared to naturally conceived children, adverse perinatal outcomes are more common among children born after assisted reproductive technology with fresh embryo transfer (fresh-ET) or frozen embryo transfer (frozen-ET). However, most previous studies could not adequately control for family confounding factors such as subfertility. We compared birth size and duration of pregnancy among infants born after fresh-ET or frozen-ET versus natural conception, using a within-sibship design to account for confounding by maternal factors. Methods and findings This registry-based cohort study with nationwide data from Denmark (1994-2014), Norway (1988-2015), and Sweden (1988-2015) consisted of 4,510,790 live-born singletons, 4,414,703 from natural conception, 78,095 from fresh-ET, and 17,990 from frozen-ET. We identified 33,056 offspring sibling groups with the same mother, conceived by at least 2 different conception methods. Outcomes were mean birthweight, small and large for gestational age, mean gestational age, preterm (<37 weeks, versus ≥37), and very preterm birth (<32 weeks, versus ≥32). Singletons born after fresh-ET had lower mean birthweight (-51 g, 95% CI -58 to -45, p < 0.001) and increased odds of small for gestational age (odds ratio [OR] 1.20, 95% CI 1.08 to 1.34, p < 0.001), while those born after frozen-ET had higher mean birthweight (82 g, 95% CI 70 to 94, p < 0.001) and increased odds of large for gestational age (OR 1.84, 95% CI 1.56 to 2.17, p < 0.001), compared to naturally conceived siblings. Conventional population analyses gave similar results. Compared to naturally conceived siblings, mean gestational age was lower after fresh-ET (-1.0 days, 95% CI -1.2 to -0.8, p < 0.001), but not after frozen-ET (0.3 days, 95% CI 0.0 to 0.6, p = 0.028). There were increased odds of preterm birth after fresh-ET (OR 1.27, 95% CI 1.17 to 1.37, p < 0.001), and in most models after frozen-ET, versus naturally conceived siblings, with somewhat stronger associations in population analyses. For very preterm birth, population analyses showed increased odds for both fresh-ET (OR 2.03, 95% CI 1.90 to 2.12, p < 0.001) and frozen-ET (OR 1.66, 95% CI 1.42 to 1.94, p < 0.001) compared with natural conception, but results were notably attenuated within siblings (OR 1.18, 95% CI 1.0 to 1.41, p = 0.059, and OR 0.92, 95% CI 0.67 to 1.27, p = 0.6, for fresh-ET and frozen-ET, respectively). Sensitivity analyses in full siblings, in siblings born within 3-year interval, by birth order, and restricting to single embryo transfers and blastocyst transfers were consistent with the main analyses. Main limitations were high proportions of missing data on maternal body mass index and smoking. Conclusions We found that infants conceived by fresh-ET had lower birthweight and increased odds of small for gestational age, and those conceived by frozen-ET had higher birthweight and increased odds of large for gestational age. Conception by either fresh-ET or frozen-ET was associated with increased odds of preterm birth. That these findings were observed within siblings, as well as in conventional multivariable population analyses, reduces the likelihood that they are explained by confounding or selection bias. Trial registration ClinicalTrials.gov ISRCTN11780826.